Pacha T'inka or La T'inka to Mother Earth in Apurímac - Valderrama, Ricardo (1976)
The community of Wirabamba (Cotabambas, Apurímac) is at 3,856 m. above sea level and its inhabitants practice a mixed agricultural and livestock economy. They are dedicated to the cultivation of bitter potatoes to produce chuño and, to a lesser extent, moraya, products that they barter for corn, wheat, and barley with those of the qheswa; or to sell or barter with the llama vendors for salt or chili. This product is basic for their economy because they always have it at their disposal, either for sale, barter or to obtain other basic products for their subsistence. They also plant for their own consumption: olluco, quinoa and ocas.